2005
DOI: 10.1063/1.1861985
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of WS2-coated multiwalled carbon nanotubes studied by energy-loss spectroscopic profiling

Abstract: We investigate experimentally the electronic properties of the coating for multiwalled carbon nanotubes covered in tungsten disulfide ͑WS 2 ͒ of various thicknesses. Coatings of thicknesses between 2 and 8 monolayers ͑ML͒ are analyzed using energy-loss spectroscopic profiling ͑ELSP͒, by studying the variations in the plasmon excitations across the coated nanotube, as a function of the coating thickness. We find a change in the ELSP for coatings above 5 ML thickness, which we interpret in terms of a change in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…In particular, Dr Vlad Stolojan at the University of Surrey has recently employed EELS to study the changes in the plasmon peak energy across the WS 2coated CNT as a function of coating thickness. Results showed that four monolayers of WS 2 are required in order that the coating approaches the WS 2 bulk dielectric state, for a WS 2 -coated MWCNT (Stolojan et al . 2004).…”
Section: Template Growth Of Nanotubes and Nanoparticlesmentioning
confidence: 99%
“…In particular, Dr Vlad Stolojan at the University of Surrey has recently employed EELS to study the changes in the plasmon peak energy across the WS 2coated CNT as a function of coating thickness. Results showed that four monolayers of WS 2 are required in order that the coating approaches the WS 2 bulk dielectric state, for a WS 2 -coated MWCNT (Stolojan et al . 2004).…”
Section: Template Growth Of Nanotubes and Nanoparticlesmentioning
confidence: 99%
“…It must be noted that here there is a physical limit on the thickness of the filler layer so that one can dielectrically define it as a layer with two surfaces, as opposed to a 'thick' interface between two media [38].…”
Section: Plasmon Localisation In 'Sandwich' Structuresmentioning
confidence: 99%